REVIEW OF THE UTILIZATION OF PALM OIL REVENUE SHARING FUNDS FOR FISCAL YEAR 2024 ON THE RESILIENCE OF THE SEI DADAP DISTRICT, ASAHAN REGENCY - Ardi Nugroho; Abdi Sugiarto; Cut Nuraini (PT. Radja Intercontinental Publishing, 2025)
This study aims to examine the Review of the Utilization of Palm Oil Revenue Sharing Funds for the 2024 Fiscal Year on the Resilience of the Sei Dadap District, Asahan Regency. This research approach is qualitative, aiming to gain an in-depth understanding of the use of Palm Oil Revenue Sharing Fund (DBH) for the 2024 Fiscal Year on regional resilience in Sei Dadap District, Asahan Regency. The location of the research was carried out in Sei Dadap District, Asahan Regency. Qualitative research data collection techniques rely on field data through interactive methods that allow direct interaction with data sources. Research Results To increase the effectiveness of DBH utilization, it is recommended that efforts be made to increase transparency, strengthen community participation in decision-making, and increase the capacity of human resources. Continuous monitoring and evaluation are also important to ensure that the use of funds is in accordance with the needs and expectations of the community. Thus, the utilization of the Palm Oil Revenue Sharing Fund in Sei Dadap District not only focuses on improving the economy, but also has a wide impact on social resilience and infrastructure, all of which contribute to the sustainable development of the region. Synergistic efforts between the government, the community, and the private sector are needed to continue to improve the results of DBH utilization for community welfare and better regional resilience in the future.